Another Extremely Strange Sum

Algebra Level 3

What is the value of n = 1 n 3 5 n 1 0 n \displaystyle\sum\limits_{n=1}^{\infty} n \cdot \dfrac{3 \cdot 5^n}{10^n} ?


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Rishabh Jain
Sep 28, 2014

the given expression can be written as 3 n = 1 n 2 n 3\sum _{ n=1 }^{ \infty }{ \frac { n }{ { 2 }^{ n } } }

now taking only the summation part which can be expanded as S = 1 2 1 + 2 2 2 + 3 2 3 + 4 2 4 + . . . . S\quad =\dfrac { 1 }{ { 2 }^{ 1 } } +\dfrac { 2 }{ { 2 }^{ 2 } } +\dfrac { 3 }{ { 2 }^{ 3 } } +\dfrac { 4 }{ { 2 }^{ 4 } } +.... => equation (1)

S 2 = 1 2 2 + 2 2 3 + 3 2 4 + 4 2 5 + . . . . \frac { S }{ 2 } \quad = \dfrac { 1 }{ { 2 }^{ 2 } } +\dfrac { 2 }{ { 2 }^{ 3 } } +\dfrac { 3 }{ { 2 }^{ 4 } } +\dfrac { 4 }{ { 2 }^{ 5 } } +.... => equation(2)

now subtract 2 from 1 and you will get simple infinite GP

thus summation part yields 2

so the final answer becomes 3 × 2 3\times 2 = 6 \boxed{6}

Did it the same way... although I didnt see the n at first so i input my answer as 3

Trevor Arashiro - 6 years, 7 months ago

This sum can be rewritten as 3 Σ n = 1 n ( 1 2 ) n 3 * \Sigma_{n=1}^\infty n*(\frac{1}{2})^{n} .

Now we know that for x < 1 |x| \lt 1 we have that Σ n = 1 x n = x 1 x \Sigma_{n=1}^\infty x^{n} = \dfrac{x}{1 - x} .

If we differentiate both sides of this equation, (term by term on the LHS), with respect to x x , we find that

Σ n = 1 n x n 1 = 1 ( 1 x ) 2 Σ n = 1 n x n = x ( 1 x ) 2 \Sigma_{n=1}^\infty n*x^{n-1} = \dfrac{1}{(1 - x)^{2}} \Longrightarrow \Sigma_{n=1}^\infty n*x^{n} = \dfrac{x}{(1 - x)^{2}} .

So with x = 1 2 x = \frac{1}{2} we find that the original sum is equal to

3 1 2 ( 1 1 2 ) 2 = 3 1 2 1 4 = 3 2 = 6 3 * \dfrac{\frac{1}{2}}{(1 - \frac{1}{2})^{2}} = 3 * \dfrac{\frac{1}{2}}{\frac{1}{4}} = 3 * 2 = \boxed{6} .

CAn you tell me how the re-writing works?

Jayakumar Krishnan - 6 years, 8 months ago

Log in to reply

First, the constant factor 3 3 can be taken outside the sum. Next, we have that

5 n 1 0 n = ( 5 10 ) n = ( 1 2 ) n \dfrac{5^{n}}{10^{n}} = (\dfrac{5}{10})^{n} = (\dfrac{1}{2})^{n} .

Brian Charlesworth - 6 years, 8 months ago

Log in to reply

Thanks :) :)

Jayakumar Krishnan - 6 years, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...